Branched glycerol dialkyl glycerol tetraethers, crenarchaeol and geochemical parameters in soils, SPM and riverbed sediments in the Godavari River basin (India) - Frédérique M S A Kirkels; Huub Michel Zwart; Muhammed Ojoshogu Usman; Francien Peterse (PANGAEA, 2021)
The concentration and fractional abundance of branched Glycerol Dialkyl Glycerol Tetraethers (brGDGTs), including 5-methyl and 6-methyl isomers, were investigated in the soils, suspended particulate matter (SPM) and riverbed sediments of the Godavari River basin, the largest non-Himalayan river in India and fed by the Southwest monsoon. Surface soils (0-10 cm) were collected near the Godavari River, and SPM and riverbed sediments were collected in a dry (February/March) and wet season (July/August) in 2015. Crenarchaeol was measured, as well as pH, TOC, and soil and sediment geochemistry.